Strategi Optimasi Penggunaan Antibiotik - Dina Fauzia (Jurnal Ilmu Kedokteran, 2015)
Use of antibiotics known is an important factor in the development of resistance tontibiotics, namely the use ofantibiotics that are inappropriate, in the form of overuse or misuse. Inappropriate use of antibiotics should be reducedto prevent the selective pressure that will lead to the development of resistance to antibiotics. Given the magnitude ofthe problem of antibiotics use in hospitals and its impact on the growing and widespread resistance to antibiotics, it isnecessary to immediately improve antibiotic use. Various strategies or interventions can be done at the hospital tooptimize the provision of antibiotics.